Respuesta :
First, you would multiply 2 by (b - 1).
Your equation will then be 3b + 2b - 2 = 8
Add the 2 like terms together:
5b - 2 = 8
Add 2 to both sides:
5b = 10
Divide 5 by both sides and you'll get b = 2.
To check this: plug in 2 for b and solve from there:
3(2) + 2(2 - 1) = 8
6 + 2(1) = 8
6 + 2 = 8
8 = 8
Your equation will then be 3b + 2b - 2 = 8
Add the 2 like terms together:
5b - 2 = 8
Add 2 to both sides:
5b = 10
Divide 5 by both sides and you'll get b = 2.
To check this: plug in 2 for b and solve from there:
3(2) + 2(2 - 1) = 8
6 + 2(1) = 8
6 + 2 = 8
8 = 8